THE WAYANG ORANG GRAHA MUSTIKA YUASTINA COMMUNITY IN SURABAYA IN THE PANDEMIC ERA: A STUDY OF VALUE, PROMOTION AND MANAGEMENET - Adi Setijowati; Rima Firdaus (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Wayang orang is a wealth of the Javanese people’ one of which is in the city of Surabaya. As a wayang community Graha Mustika Yuastina is a recognized community in the city of Surabaya. As evidenced by the frequent performances in the Cak Durasim building which is sponsored by the Surabaya Cultural Center. Covid 19 which prohibitis crowds has a real impact on this community, especially in terms of staging. The inevitable impact is that the performance is postponed. This happanned because of diversion ofart funds, the mayority of which were used to overcome the pandemic .in an indepth interview, it was stated that this wayang orang performance had to change the platform in this pandemic era, namely from classical style performance to youtube and Instagram. This will affect the media promotion. As for the values of wayang still trying to be maintained.